The Address in the Contemporary Iraqi Poetry: Selected Samples from Basra Poets - Hamed Abd al-Samad , Lect .Dr. Wurood (Basra studies journal, 2024)
The title serves as a crucial indicator for reconstructing the text and comprehending its content by arranging the meaning points into an integrated framework. It underscores the effectiveness of communication with the reader by offering interpretations and suggestions that foster a balance and resonance with the reader's psychological state and cultural background, thereby contributing to an understanding of the text. The title plays a central role in achieving balance and coherence, helping to reveal the meanings and ideas embedded within the text.